Left atrial appendage occlusion in octogenarians - Gafoor, Sameer; Franke, Jennifer; Bertog, Stefan; Boehm, Patrick; Heuer, Luisa; Gonzaga, Maik; Bauer, Janine; Braut, Annkathrin; Lam, Simon; Vaskelyte, Laura; Hofmann, Ilona; Sievert, Horst (Catheterization and cardiovascular interventions, 2014)
To determine the procedural safety, safety, and efficacy of left atrial appendage (LAA) occlusion in octogenarians. Background Elderly patients with atrial fibrillation (AF) often do not receive appropriate anticoagulation. LAA occlusion is an option for patients with AF and contraindications to anticoagulation. Not much is known about the procedural safety and clinical efficacy of LAA occlusion in the very elderly.